Methodology for the identification of priority areas for post-fire restoration: study of the Sierra Bermeja forest fire 2021 - Perales-Vallejo, Manuel J.; Hueso-González, Paloma; Ruiz-Sinoga, José Damián (Revista de Estudios Andaluces, 2025)
The objective of this study is to develop a preliminary methodology to identify priority areas for post-fire restoration in the aftermath of the forest fire that occurred in Sierra Bermeja (province of Málaga) in 2021. The fire impacted a serpentine environment and was one of the most significant fires in recent decades in the province of Málaga, burning 8,401 hectares. To delineate the priority action areas, a multi-criteria methodology was employed, combining remote sensing techniques, soil sampling and analysis, and models for calculating erosion rates. All these elements were integrated into a GIS environment. The results of the proposed methodology reveal that three areas of Sierra Bermeja exhibit significant fire severity and face severe challenges in natural regeneration due to their impact on soils, vegetation cover, and high erosion rates.